Mathematical forms of Planck’s thermal radiation law and photobiological biomass adaptations - Mariana Sendova; Isaac Moncada-Almendarez (Academia Biology)
Solar photons with energies from 1.2 to 3 eV fuel Earth’s biosphere via excited-state photochemical reactions. The solar radiance spectrum is successfully modeled by Planck’s thermal radiation law, applied to a blackbody heated to ~5,800 K. Mathematically, Planck’s thermal radiation law can be described by four distinct, bell-shaped radiance probability density functions. This study attempts to answer the question: Which one of the four distinct radiance spectral functions, representing one and the same thermal radiation law, is synergistic with the established photobiological adaptations on Earth? A well-defined quantitative criterion is proposed to select one of the four functions. The data suggest that the photon radiance per wavelength increment provides a deeper biophysical understanding of the broad range of photobiological biomass adaptations on Earth.